ANALISIS PENGENDALIAN PRODUKSI DAN PERSEDIAAN PRODUK MIE PADA UKM MIE GAJAH MADA - Esrawati Esrawati; Bahariandi Aji Prasetyo (Computer Science and Industrial Engineering, 2026)
UKM Mie Gajah Mada is a small and medium enterprise located in Kavling Bintang, Batam. The company grapples with major production management challenges, as scheduling relies heavily on managerial intuition rather than data, often resulting in inventory depletion. To address this, the study employs Weighted Moving Average (WMA) and Double Exponential Smoothing (DES) to project product demand. The research aims to establish an optimal inventory control system by selecting the best forecasting technique and applying Economic Order Quantity (EOQ), Safety Stock, and Reorder Point (ROP) models. Findings reveal that the 5-period WMA is the most accurate approach according to MAD, MSE, and MAPE indicators. With demand forecasted to fluctuate between 12,815.3 and 2,598 units from April to July, these calculations offer a systematic guide for raw material procurement, helping the firm mitigate the risks of both excess inventory and stock shortages